Maternal homework assistance and children's task-persistent behavior in elementary school. (August 2018) - Viljaranta, Jaana; Silinskas, Gintautas; Lerkkanen, Marja-Kristiina; Hirvonen, Riikka; Pakarinen, Eija; Poikkeus, Anna-Maija; Nurmi, Jari-Erik
Abstract: The present study used a sample of 365 children to investigate the longitudinal associations between maternal homework assistance (i.e., help, monitoring, and autonomy granting) and children's task-persistent behavior in learning situations from grade 2 to grade 4 of elementary school. Also, the extent to which task-persistent behavior plays a role in the links between parental homework assistance and children's academic performance was examined. The results showed that the more autonomy granting mothers reported, the more task-persistent behavior children exhibited; and more task-persistent behavior children exhibited, the more autonomy their mothers granted. In contrast, the more mothers helped their children, the less task-persistent behavior was reported, and the less task-persistent behavior children exhibited, the more mothers tried to help and monitor their children later on. Additionally, some evidence was found supporting the role of task-persistent behavior in the relation between maternal homework assistance and academic performance. Highlights: Mother's homework assistance was related to child's task persistence. Autonomy granting was related to exhibiting higher levels of task persistence. Help was related to exhibiting less task-persistent behavior. Child's task persistence contributed on mothers' homework assistance. The results indicate that not all assistance leads to positive outcomes.